Aesop's fables - Santore, Charles (Little Apple classics., 2019)
The world's best-known children's fables now in the perfect size for little hands and big imaginations. These classic tales of memorable and adorable creatures learning right from wrong are the perfect way to introduce children to concepts of conscience, kindness, and empathy.